Variation in the ICAM1-ICAM4-ICAM5 locus is associated with systemic lupus erythematosus susceptibility in multiple ancestries (2012)
Objective: Systemic lupus erythematosus (SLE; OMIM 152700) is a chronic autoimmune disease for which the aetiology includes genetic and environmental factors. ITGAM, integrin ?M(complement component 3 receptor 3 subunit) encoding a ligand for intracellular adhesion molecule (ICAM) proteins, is an established SLE susceptibility locus. This study aimed to evaluate the independent and joint effects of genetic variations in the genes that encode ITGAM and ICAM. Methods: The authors examined several markers in the ICAM1-ICAM4-ICAM5 locus on chromosome 19p13 and the single ITGAM polymorphism (rs1143679) using a large-scale case-control study of 17 481 unrelated participants from four ancestry populations. The singlemarker association and gene-gene interaction were analysed for each ancestry, and a meta-analysis across the four ancestries was performed. Results: The A-allele of ICAM1-ICAM4-ICAM5 rs3093030, associated with elevated plasma levels of soluble ICAM1, and the A-allele of ITGAM rs1143679 showed the strongest association with increased SLE susceptibility in each of the ancestry populations and the trans-ancestry meta-analysis (ORmeta=1.16, 95% CI 1.11 to 1.22; p=4.88 × 10-10 and ORmeta=1.67, 95% CI 1.55 to 1.79; p=3.32 × 10-46, respectively). The effect of the ICAM single-nucleotide polymorphisms (SNPs) was independent of the effect of the ITGAM SNP rs1143679, and carriers of both ICAM rs3093030-AA and ITGAM rs1143679-AA had an OR of 4.08 compared with those with no risk allele in either SNP (95% CI 2.09 to 7.98; p=3.91 × 10-5). Conclusion: These findings are the first to suggest that an ICAM-integrin-mediated pathway contributes to susceptibility to SLE.